STRATEGY FOR THE DEVELOPMENT OF PROFESSIONAL ABILITIES FOR AAL OF ENGINEERING CORPS USING IPA, SWOT AND ISM METHODS - Juni Hari Budianto; Suparno Suparno; Anton Nugroho; Mukhlis Mukhlis (JOURNAL ASRO, 2021)
Mechanical engineering corps of Indonesian Naval Cadets Department in charge of producing professional Engineering Corps Officers with knowledge and skills in the field of Indonesian Navy logistics management and warship engine engineering. There were still some of the obstacles that exist in the Study Program will certainly have an impact on the performance displayed by the graduates in their duties. This study used the IPA (Importance Performance Analysis) method to see the performance of graduates, the SWOT (Strength, Weakness, Opportunities and Threat) method in formulating strategies and the ISM (Interpretative Structural Modeling) approach in determining priorities and strategy mapping with the aim of producing a roadmap of chosen strategy. The results showed that the mapping of the position of the performance attributes of graduates in the Quadrant Analysis and the level of satisfaction at the level was quite satisfied with a satisfaction score of 63.6%. By using ISM method approach, five levels of hierarchical structure are generated to be used as a reference in determining the roadmap for the professional development strategy of the engineering corps of Indonesian Naval Cadets. Keywords: Engineering corps of Indonesian Naval Cadets Department, IPA, SWOT, and ISM